Use of AI in Market Research (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Artificial Intelligence in Marketing is a rapidly emerging field that is transforming the way businesses approach their marketing strategies. Second, the researcher employed a qualitative study strategy that included semi-structured interviews with marketing professionals from several Indian companies. The researcher chose a sample size of fifteen marketing experts to interview. It involves the use of Artificial Intelligence (AI), Machine Learning (ML), and other advanced technologies to automate and optimize various marketing processes. its benefits and challenges, best practices for implementation, and ethical considerations. It will also look into the future of Artificial Intelligence in Marketing and its potential impact on the marketing landscape.